International trade barriers and regional employment: The case of a no-deal Brexit - Hans-Ulrich Brautzsch; Oliver Holtemöller (Journal of Economic Structures, 2021)
We use the World Input-Output Database (WIOD) combined with regional sectoral employment data to estimate the potential regional employment effects of interna-tional trade barriers. We study the case of a no-deal Brexit in which imports to the United Kingdom (UK) from the European Union (EU) would be subject to tariffs and non-tariff trade costs. First, we derive the decline in UK final goods imports from the EU from industry-specific international trade elasticities, tariffs and non-tariff trade costs. Using input-output analysis, we estimate the potential output and employment effects for 56 industries and 43 countries on the national level. The absolute effects would be largest in big EU countries which have close trade relationships with the UK, such as Germany and France. However, there would also be large countries outside the EU which would be heavily affected via global value chains, such as China, for exam-ple. The relative effects (in percent of total employment) would be largest in Ireland followed by Belgium. In a second step, we split up the national effects on the NUTS-2 level for EU member states and additionally on the county (NUTS-3) level for Ger-many. The share of affected workers varies between 0.03% and 3.4% among European NUTS-2 regions and between 0.15% and 0.4% among German counties. A general result is that indirect effects via global value chains, i.e., trade in intermediate inputs, are more important than direct effects via final demand.
Keywords: C67; D57; F16; R15; 330; Brexit; Employment; European Union; International trade; Tariffs; Trade barriers